2001
DOI: 10.1002/1099-0690(200106)2001:11<2035::aid-ejoc2035>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Azaenolates of 2-Chloromethyl-4-methoxymethyl-5-phenyl-2-oxazoline − A Highly Diastereo- and Enantioselective Synthesis of Oxazolinyloxiranes

Abstract: The oxazoline‐derived titanium azaenolate 6 couples highly stereoselectively with aldehydes affording highly optically pure oxazolinyloxiranes 7. The epoxide 7a has been deblocked to form the optically pure formyl oxirane 9. In contrast, the corresponding boron azaenolates 2 and 3 couple with very poor or no stereoselectivity. Lithium, aluminum and tin azaenolates have also been shortly studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The ( S , S ) absolute configuration of the major diastereomer of oxazolinyloxirane (−)- 1e (dr 98/2) was deduced by combining the results of a 2D-NOESY Phase-Sensitive experiment and calculations (see Supporting Information) and was in agreement with what reported for other optically active oxazolinyloxiranes prepared as just described for (−)- 1e (see ref ).…”
Section: Referencessupporting
confidence: 81%
See 1 more Smart Citation
“…The ( S , S ) absolute configuration of the major diastereomer of oxazolinyloxirane (−)- 1e (dr 98/2) was deduced by combining the results of a 2D-NOESY Phase-Sensitive experiment and calculations (see Supporting Information) and was in agreement with what reported for other optically active oxazolinyloxiranes prepared as just described for (−)- 1e (see ref ).…”
Section: Referencessupporting
confidence: 81%
“…We reasoned it could be done using a chiral oxazolinyloxirane as the starting material. Enantiomeric oxazolinyloxiranes (+)- and (−)- 1e 12 (Schemes and ) were prepared starting from the chiral 2-chloromethyl-2-oxazolines (+)- and (−)- 9 by lithiation followed by lithium−titanium transmetalation as similarly reported . Then, the oxazolinyloxirane ( S , S )-(−)- 1e (dr 98/2, ee > 99%, [α] D −79) was lithiated and reacted with 3a to give the optically active (3 R ,4 R ,7 S ,11 S ) - ( + ) - 4i as a single diastereoisomer in a very good yield (75%) (Scheme ).…”
mentioning
confidence: 99%
“…In general, 3-halo-1-azaallylic anions 5 are mostly synthesized using lithium diisopropylamide (LDA) as a base for the deprotonation of the starting imines 4 . However, to influence the structural, coordination, and reactivity properties of 1-azaallylic anions and to increase the stereoselectivity in organic reactions with these species and related enolates, such as additions across aldehydes or imines, , it can be of considerable benefit to introduce another metal counterion to the anion (as shown above for the zincated 3-chloro-1-azaallylic anion). ,, The addition of a salt of the desired counterion to the lithiated anions will result in the transmetalation of the starting 3-halo-1-azaallylic anions. In this part, the driving force for the transmetalation reaction will be discussed.…”
Section: Resultsmentioning
confidence: 99%
“…Recent investigations [1][2][3][4][5][6][7][8][9][10][11] have shown that 1,3-oxazolines (4,5-dihydro-oxazoles or 2-oxazolines)…”
Section: Introductionmentioning
confidence: 99%